2002
DOI: 10.1074/jbc.m108944200
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome cd1, Reductive Activation and Kinetic Analysis of a Multifunctional Respiratory Enzyme

Abstract: Paracoccus pantotrophus cytochrome cd 1 is an enzyme of bacterial respiration, capable of using nitrite in vivo and also hydroxylamine and oxygen in vitro as electron acceptors. We present a comprehensive analysis of the steady state kinetic properties of the enzyme with each electron acceptor and three electron donors, pseudoazurin and cytochrome c 550 , both physiological, and the non-physiological horse heart cytochrome c. At pH 5.8, optimal for nitrite reduction, the enzyme has a turnover number up to 121 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
79
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 44 publications
(82 reference statements)
4
79
1
Order By: Relevance
“…Pseudoazurin (PAz) is proposed to be one of the electron carriers in the periplasm of the bacteria, shuttling electrons between the cytochrome bc 1 complex and several periplasmic enzymes involved in denitrification as well as CCP [14,15]. Another small redox protein, cytochrome c 550 , has also been identified as the electron donor to these enzymes [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Pseudoazurin (PAz) is proposed to be one of the electron carriers in the periplasm of the bacteria, shuttling electrons between the cytochrome bc 1 complex and several periplasmic enzymes involved in denitrification as well as CCP [14,15]. Another small redox protein, cytochrome c 550 , has also been identified as the electron donor to these enzymes [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The switch to His/Met ligation significantly raises the reduction potential of heme c, more closely matching the donor proteins cytochrome c 550 and pseudoazurin (8 -13). This led to the speculation that this facilitates electron transfer (8) but a low heme c potential is not strictly an obstacle because the overall electron transfer from donors to NO 2 Ϫ is thermodynamically favorable (13,14). The purpose of the ligand switch is therefore unclear.…”
mentioning
confidence: 99%
“…Until this reversion has occurred, the enzyme is capable of NO 2 Ϫ reduction using the physiological electron donor pseudoazurin (11). It is reported that for full activity, oxidized Pp cd 1 requires preactivation by chemical reduction (11,13). Consequently, His/Met ligated heme c is presumed to be a prerequisite of activity, and it has been proposed that the oxidized enzyme is a resting form bypassed in catalysis as the enzyme cycles rapidly compared with the rate of reversion to the His/His form (13,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In nitrite reductase assays, turnover occurs at approximately 10 2 s À1 [37]. Fourier transform infrared (FTIR) studies show that the initial reaction with nitrite proceeds with k > 500 s À1 and a subsequent rearrangement occurs in approximately 40 ms [38].…”
Section: Assessing the Efficiency Of Reagent Injection And Stirring Mmentioning
confidence: 99%